2006
DOI: 10.1590/s0073-47212006000400014
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology in the small neotropical amphisbaenid Amphisbaena munoai (Amphisbaenidae) in southern Brazil

Abstract: ABSTRACT. We analyzed the alimentary tract of 66 specimens of Amphisbaena munoai Klappenbach, 1969 from the Serra do Sudeste, state of Rio Grande do Sul, southern Brazil. Forty specimens (60.6%) had prey items in their gut. The diet consisted mainly of small invertebrate prey, such as termites, insect larvae and ants. The most abundant prey item was termites, found in 62.5% of the non empty stomachs. The high number of individual prey items in the majority of stomachs, the small size of the regular prey items,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 9 publications
2
18
0
4
Order By: Relevance
“…Interestingly we recorded workers of the epigaeic Eciton and Labidus praedator (Ecitoninae) in the stomach contents of amphisbaenian reptiles, which indicate that amphisbaenians forage also on the soil surface, as suggested by Bernardo- Silva et al (2006) and observed by Gorzula et al (1975). Also, one of the ant individuals found in the stomach contents of an Amphisbaena alba is a large soldier of Eciton mexicanum, suggesting also that these reptiles are not reluctant to invest against potentially aggressive ants.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Interestingly we recorded workers of the epigaeic Eciton and Labidus praedator (Ecitoninae) in the stomach contents of amphisbaenian reptiles, which indicate that amphisbaenians forage also on the soil surface, as suggested by Bernardo- Silva et al (2006) and observed by Gorzula et al (1975). Also, one of the ant individuals found in the stomach contents of an Amphisbaena alba is a large soldier of Eciton mexicanum, suggesting also that these reptiles are not reluctant to invest against potentially aggressive ants.…”
Section: Discussionsupporting
confidence: 75%
“…Several behavioral associations have been reported between ants and different reptiles, such as predation (Riley et al, 1986;Cruz-Neto & Abe, 1993;Barros Filho & Valverde, 1996;Colli & Zamboni, 1999;Kearney, 2003;Wetterer & Moore, 2005;Staller et al, 2005;Bernardo-Silva et al, 2006;Whitfield & Donnelly, 2006;Goldsbrough et al, 2006), and inquilinism (Brandão & Vanzolini, 1985;Riley et al, 1986;Oliveira & Della Lucia, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Information about the natural history of A. munoai was presented by BERNARDO-SILVA et al (2006), who studied the diet of the species in an area close to where the present study was developed (Escudo Sul-RioGrandense). Nothing was known until now about the reproduction of this species.…”
Section: Balestrin and Cappellarimentioning
confidence: 99%
“…This is one of the highest amphisbaenian diversity in the world (80% of South American species and 35% of world species) (GANS, 2005) but the natural history of this group has been little explored (e.g. BARROS FILHO & VALVERDE, 1996;COLLI & ZAMBONI, 1999;ANDRADE et al, 2006;BERNARDO-SILVA et al, 2006). On the other hand, regions of temperate climate, mainly in North America, Europe and Australia, although less diverse, revealed Squamata reptile species that were good models for studies emphasizing natural history, related to the easy observation/capture and to the relative frequency (SEIGEL & COLLINS, 1993).…”
mentioning
confidence: 99%